Justice Beyond Legal Formalism: A Maslahah-Oriented Reading of Criminal Law Enforcement in Indonesia through Rawls and Hamka - Moh Safik; Mu’tashim Billah (Rule of Law Studies Journal, 2025)
Background: Criminal law enforcement in Indonesia is still widely understood as a matter of procedural compliance and formal proof, while the dimension of justice experienced by society often remains marginal. Aims: This article aims to reread criminal law enforcement by positioning maslahah as an evaluative horizon and placing it in dialogue with the ideas of justice developed by John Rawls and Buya Hamka, in order to articulate a more humane and equitable normative direction. Methods: This study adopts a qualitative normative–philosophical approach based on library research. The analysis draws on major works by Rawls and Buya Hamka, supported by literature on criminal law enforcement and maslahah theory. Analytical reasoning is guided by the concepts of maslahah mursalah and maslahah mu‘tabarah to assess legal objectives, public benefit, and potential harm within criminal law practices. Result: The analysis reveals that criminal law enforcement in Indonesia tends to prioritize procedural legality and punishment, while insufficiently addressing the protection of vulnerable groups and the restoration of social balance. A maslahah-oriented reading highlights the need to consider public benefit, harm prevention, and the safeguarding of human dignity as more adequate criteria for evaluating criminal law enforcement. Conclusion: Moving beyond legal formalism requires an ethical framework capable of bridging distributive justice and conscience-based justice. Anchored in maslahah, the conceptual dialogue between Rawls and Hamka provides a normative foundation for strengthening substantive justice and enhancing the legitimacy and public trust of Indonesia’s criminal justice system.